Phthalimide-based-SSCF3 reagent for enantioselective dithiotrifluoromethylation. Issue 6 (2nd February 2021) - Gao, Wen-Chao; Liu, Jianrong; Jiang, Xuefeng
Abstract : A novel dithiotrifluoromethylation reagent phthN-SSCF3 was designed and prepared for the incorporation of a SSCF3 unit into complex molecules and the stereoselective construction of a SSCF3 -tethered quaternary carbon center. Abstract : An electrophilic phthalimide-based-SSCF3 reagent was designed and prepared for straightforward SSCF3 incorporation of diverse β-keto esters in natural products, pharmaceuticals and biological molecules. The asymmetric dithiotrifluoromethylation was achieved with a good to excellent enantioselectivity, catalyzed by a cinchona-alkaloid-based catalyst (DHQD)2 PHAL via an ammonium-hydrogen-bonded induction mode.